Kumlarda denge durumu - Değerli, Mahmut (Fen Bilimleri Enstitüsü, 1996)
Bu araştırmada suya doygun, temiz kumların basit kesme deney sisteminde statik yükler altında davranış biçimleri ve bu davranış biçimi üzerinde konsolidasyon basıncının ve relatif sıkılığın etkisi incelenmiştir. Laboratuvarda hazırlanmış temiz ona kumlar üzerinde deformasyon kontrollü olan statik basit kesme deney sisteminde bir seri deney yapılmıştır. Sonuçlar, relatif sıklığın artması ile denge durumundaki kayma direncinin artmakta olduğunu göstermiştir. Yine aynı şekilde konsolidasyon basıncının artması ile kayma direncininn arttığı görülmüştür. Ayrıca relatif sıkılığın azalması durumunda denge durumunun daha küçük birim kayma deformasyon değerlerinde olduğu bulunmuştur. Diğer bir sonuç ise kayma gerilmesi ile efektif gerilmenin değişim eğrisinin yatayla yaptığı açı 32 °'dir.

Soil as a material is the composite of the rocks that are weathered un der different environmental conditions. The mechanical ör chemical agents, erosion, transportation, deposition and compression by later sediments are the natural cycle of weathering of Earth's crust. Since soil is formed by the weathering of rocks the soil grains will consist of the basic rock-forming minerals ör their products after chemical alternation. If rocks are only physically degraded by the motion of içe, water ör air the soil grains will have the same composition as the parent rock. The size, shape and texture of the mineral grains will depend primarily on the history of degradation, transportation and deposition. When chemical changes occur, the basic rock-forming minerals may be changed to the day minerals. Civil engineers are interested in the design and the construction and are oblıged to perform safety and serviceability of the engineering structure. A geotechnical engineer must be concerned with the mechanical behaviour of the soil more than the microscopic properties. Testing the samples in the laboratory plays an important role in soil mechanics research and civil engineering practice. Laboratory tests are applied on small samples of soil to examine the characteristics of soil ör on models of soil structures to examine how slopes, walls and foundation deform and collapse. The extensive damages resulting from soil liquefaction in recent earthquakes have re- emphasised the need for reliable procedures for predicting the possible development of this phenomenon. Studies of the types of soil which have liquefied dunng earthquakes, laboratory investigations of the factors inducing liquefaction of saturated sands under cyclic loading conditions, and analytical procedures for predicting the liquefaction potential of sand deposits have throvvn considerable light on the subject. Liquefaction of loose and saturated sands may be caused by cyclic ör static (monotonically increasing) undrained loading. The behaviour of such sands under cyclic loading has received a great deal of artention from researchers since the dramatic effects of liquefaction \vere observed in Niigata, Japan (Japan National Committee 1966; Ohsakı 1966) and Alaska (Grantz et al. 1964, Seed and VVilson 1967) dunng earthquakes in 1964 Stımulated by the need for evaluation of the potential for lıquefactıon affecting cntical structures such as nuclear po\ver plants. the liquefaction behavıour of sands under cyclic loading conditions has become relatively well understood.The liquefaction behavıour of sands under static loading conditions. however, has received considerably less attention, though extremely important laboratory studies of this phenomenon have been made in the past 20 years by Castro and Poulos The research described in this paper is concerned with the steady state of sands. For purposes of clarification, the following terminology will be used here in. The state of a sand is the description of the physical conditions under which it exists. Void ratio (ör density) and stress are the primary state variables for soils. Fabric is also a state variable of importance, while temperature, for example, is of little importance for sands. The steady state of deformation for any mass of particles is that in which the mass is continuously deforming at constant volume, constant normal effective stress, constant shear stress, and constant velocity. The steady state of deformation is achieved only after ali partide orientation has reached a statistically steady state condition and after ali partide breakage, if any, is complete, so that the shear stress needed to continue deformation and the velocity of deformation remain constant(Poulos 1981). The steady state deformation requires a constant velocity of deformation and the steady state exists only so long as deformation continues. The critical state has been defined as the state at which the soil continues to deform at constant stress and constant void ratio(Roscoe 1958). The steady state has traditionally been measured using undrained tests on loose sand samples. While the critical state is generally inferred from drained tests on dense sands. Poulos (1981) has pointed out that the critical and steady states differ in that the steady state, by definition, has an associated flow structure and a requirement for a constant velocity, neither of which are incorporated in critical state concepts. These differences are in definition, but the particular flow structure and applicable strain rate have not been defined. This makes a clear distinction of the steady state from the critical state impossible. The authors are not aware of any data demonstrating flow structures in sands on a particular scale, ör of data shovving that constant velocities actually occur in load-controlled liquefaction tests. Based on recent investigations it seems reasonable to conclude that steady state characteristics of a sand, in-situ are influenced by the various factors 1) Sample Preparation Methods 2) Loading velocity 3)Loadıng Systems 4) Gram size dıstribution and grain shape 5) Stress history 6) Relative density 7) Confinıng Pressure 8) Fires Content When compared with the hydraulic system, samples sheared with the dead-load apparatus exhibited lower residual or steady-state deviatoric stresses for a given sample preparation method. Furthermore, the steady state was achieved and maintained over a greater with this apparatus. It also maximised steady-state velocity potentials during flow compared with the hydraulic loading unit. The relative position of the steady-state curve was influenced by the sample preparation method and not by the type of loading system, Hence, the same peak pore-water pressure response for a given sample preparation method was generated with both loading systems (DeGregorio 1990). Samples prepared by dry pluviation, moist tamping, and moist vibration, in that order, exhibited progressively higher peak and steady-state strengths when sheared with the dead-load device. In addition, dry pluviated specimens displayed a greater peak pore- water pressure response than specimens prepared by either moist methods (DeGregorio, 1990) The static liquefaction resistance, defined as the shear stress increase under undrained conditions required to initiate liquefaction was consistently observed to increase with the increasing relative density and confining pressure, and to decrease with the increasing initial shear stress level (S. Kramer, B. Seed, 1988). The steady-state strength of the over consolidated samples decreases with the decreasing effective confining stress. The peak strength simultaneously decreases with the decreasing confining stress in the normally consolidated samples. The potential for initiation of liquefaction can be considered to decrease with the increasing effective confining pressure. In order to explain the mechanism of the steady state of sands, extensive experimental studies have been conducted on reconstituted sand samples. In these studies it was observed that the method of sample preparation strongly affects the steady state of sands and there are some difficulties about sample preparation for sands in a wide range of gradation and density. In addition to the other problems associated with reconstituted samples, the lack of in-situ stress history that leads to over-estimation of steady state strength is another problem. In this research, undrained behaviour of saturated sands under static loads and the effects of relative density and confining pressure have been studied based on reconstituted samples A series of tests is carried out with static simple shear test device. The static simple shear testing system used in this study is a modified version of Norwegian simple shear apparatus, developed by Prof Ishihara and Prof Silver The static simple shear testing system is a strain controlled system. The horizontal strains are applied as strain-controlled at the top cap connected to a horizontally moveable shaft going through the cell. The test sample has 70mm diameter and a 30mm height, and can be consolidated under both isotropic stresses, and anisotropic stresses The X11I shear stresses, the pore pressures and the axial and horizontal deformations are measured by sensitive displacement transducers located apart from the chamber. In this study, the method adopted to obtain sample is based on dry pluviation. Reconstituted samples are prepared by the method of pluviation in water. A vacuum apporoximetely 20*30 kPa was applied to clean sand samples. In order to have the samples saturated, long term vacuum was applied. Dimensions of the sample were re-measured to calculate the thawed unit weight. The test chamber was assembled and filled with viscous oil. The air in the pores is removed by circulating water from bottom to top under vacuum. Then vacuum gradually reduced to zero while simultaneously increasing the cell pressure to a value 30 kPa. Cell pressures and back pressures were increased while maintaining the constant effective confining stress. The sample was allowed to stabilise at this stress level for 24 hours. In most cases B value (AU/Aoc) was obtained as 0.98 or greater after 24 hours. Uniform clean sand has mean grain size D.so, 0.60mm. The coefficient of uniformity, Cu, is 1.44 and, Cc, is 1.03. The minimum void ratio of clean sand, e"un, is 0.48 and the maximum void ratio of clean sand, emax, is 0.749. In this study, aim was to investigate the effects of relative density and confining pressure on clean sands. The result of undrained static simple shear tests on reconstituted sandy samples are the following conclusions 1. The increase in relative density increases the steady state strength. 2. The increase in confining pressure increases the steady state strength 3. The tangent of the stress path curve is 32°. 4. The steady state line of this sand is drawn depending upon the test results. Since the relative densities of the samples are very great, the steady state line of these samples is very steep. Finally, it would seem that the design engineering confronted with the need to evaluate the possible steady-state potential of a sandy sand soil has three choices 1. Taking the best possible undisturbed samples and then trying to reconstruct their true field characteristics. 2 Devising and utilising a procedure such as freezing the samples during sampling and handling and thawing them prior to testing m order to possibly maintain soil density and structure, however, the use of such a procedure still requires investigation as to its usefulness XIV 3. To be guided by the known field performance of sands correlated with some measure of in-situ characteristics, such as the standard penetration test. Most of the factors that tend to improve the steady state strength also tend to increase the standard penetration resistance or the results of any other in-situ test that may be adopted as a possible indicator of field steady state behaviour.
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1996
Keywords: Denge; Jeoteknik; Kum; Equilibrium; Geotechnics; Sand